Exploring New Directions for the Transformation of the Built Environment in Nigeria: The Role of Building Information Modeling (2016)
Building Information Modelling (BIM) offers an alternative and better method of handling information for integrated project delivery approach to that of the traditional fragmented method of collaboration in the built environment. This paper is aimed at assessing the awareness and the prospects of adopting BIM in the professional Architectural practices in Nigeria using Akure as a case study. The rate of urbanisation and transformation of the built environment in the face of globalisation, calls for a new direction in the processing and handling of building information. This is particularly necessary as the current business model is inadequate for maximum productivity. The field investigation focused on determining the current business model of selected Architectural practice as well as assessing their awareness of Building Information Modelling and whether or not professionals are going to adopt it soon. The findings showed that the method of collaboration among professionals remain fragmented, the use of 3D software and even BIM software is limited to just 3D visualization and plan details. The study revealed that despite a good number of respondents already conscious of the benefit of using a BIM tool; their overall approach to project delivery remains fragmented. Awareness of the concept of BIM was a little above average among respondents but BIM implementation in professional practice is very low. It was discovered that challenges faced by respondents in the adoption of BIM is predicated on the attitudinal disposition of other professionals with whom they work and exchange building information with. These professionals do not work with BIM and coupled with inadequate knowledge of staff in the adoption of BIM workflow. The paper concluded that Building Information Modelling (BIM) has greater advantage than the existing traditional practice involving 2D drafting. BIM also has the inherent ability to foster integrated project delivery by creating a common platform for all professionals to work simultaneously on a project thereby minimising costly design and construction errors